2014
DOI: 10.3766/jaaa.25.10.6
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Speech-In-Noise Recognition: The Role of Proactive Interference

Abstract: The results show that capacity to resist semantic PI can be used to predict SIN recognition scores in young listeners with normal hearing. On the basis of these findings, future research will focus on investigating whether tests of PI can be used in the treatment and/or rehabilitation of hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
(45 reference statements)
0
12
2
Order By: Relevance
“…Proactive interference refers to the degradation of memory traces by prior encoded information (Kane and Engle, 2000 ), particularly items with a similar context—such as, words within the same category in a closed set corpus. The ability to resist semantic proactive interference has been shown to be closely related to speech in noise recognition (Ellis and Rönnberg, 2014 ). Differences in this study in the level of proactive interference between high and low working memory participants may mediate cross-trial or within-trial interference and hence the accuracy of recall.…”
Section: Discussionmentioning
confidence: 99%
“…Proactive interference refers to the degradation of memory traces by prior encoded information (Kane and Engle, 2000 ), particularly items with a similar context—such as, words within the same category in a closed set corpus. The ability to resist semantic proactive interference has been shown to be closely related to speech in noise recognition (Ellis and Rönnberg, 2014 ). Differences in this study in the level of proactive interference between high and low working memory participants may mediate cross-trial or within-trial interference and hence the accuracy of recall.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, inhibitory control is, unlike WMC, important when as much as 50% of the information is lost due to adverse listening conditions, whereas WMC is especially important for 80% speech intelligibility. In a study by Ellis and Rönnberg (), the authors used a 2‐talker semantically meaningful speech as masker, whereas this study used a slightly modulated speech‐shaped noise as masker. This study also used a different speech material than Ellis & Rönnberg () did.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ellis and Rönnberg (), the authors used a 2‐talker semantically meaningful speech as masker, whereas this study used a slightly modulated speech‐shaped noise as masker. This study also used a different speech material than Ellis & Rönnberg () did. However, in line with the results in this study, they showed that capacity to resist semantic interference can be used to predict performance in a speech‐in‐noise‐task.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory control is the ability to control impulses and undesired activity. This ability seems to be important in listening tasks where a target signal needs to be followed while ignoring task-irrelevant input (Engle, 2002;Diamond, 2013;Ellis and Munro, 2013;Ellis and Rönnberg, 2014). In line with this, inhibitory control has been shown to be related to better speech recognition performance in noise for adults with normal hearing (Stenbäck et al, 2015;2016).…”
Section: Introductionmentioning
confidence: 82%